DETERMINANTS OF WORK EFFECTIVENESS THROUGH EDUCATIONAL IMPROVEMENT - Yasmir Lukman; Kiki Farida Ferine (Universitas Efarina, 2025)
This study aims to analyze the effect of the number of employees and competence on work effectiveness with education as a moderating variable among employees of the Trade and Customer Management Division as well as the Finance, Communication, and General Division at PT PLN (Persero) North Sumatra Distribution Main Unit. The research problem arises from the importance of work effectiveness in supporting the company's operational sustainability, particularly in the electricity distribution sector, which requires efficiency, service quality, and employee performance accuracy. This research employs a quantitative approach using a survey method. The population consists of all employees in the observed divisions, with a total sample of 94 respondents determined through a saturated sampling technique. The research instrument was a questionnaire using a Likert scale. Data were analyzed using Partial Least Square (SmartPLS 3.0). The results indicate that: (1) the number of employees has a positive and significant effect on work effectiveness; (2) competence has a positive and significant effect on work effectiveness; (3) education does not moderate the relationship between the number of employees and work effectiveness; and (4) education does not moderate the relationship between competence and work effectiveness. The R-Square value of 0.693 shows that the variation in work effectiveness can be explained by the number of employees and competence by 69.3%, while the remaining percentage is influenced by other factors outside this research model. These findings highlight the importance of maintaining a proportional number of employees and enhancing employee competence to improve work effectiveness. However, education as a moderating variable was not proven to have a significant role in this study.